ANALISIS IMPLEMENTASI PEMBERIAN PINJAMAN BERGULIR PNPM MANDIRI PERKOTAAN KEPADA USAHA KECIL DAN MENENGAH DI DESA BULUSULUR KECAMATAN WONOGIRI KABUPATEN WONOGIRI - Leo Giri Sasana; Kushandajani .; Achmad Taufiq (Journal of Politic and Government Studies, 2014)
Eradicating poverty is one of the main case in Indonesian lifelihood. Sincethe independence day of Indonesia's republic. The exertions to increased life'squality and eradicating poverty always efforted by them till this recent time. Itsthroughed by PNPM urban private. Based on empowerement which has purposesas sustaiable development and can be synergized through societies withinpoverty's problem solving. This research is limited by limitation space and alsofactors which can be called as obstacle of implementation in Wonogiri regency.Particularly in Bulusulur village. This research uses descriptive qualitative bycollege data technique through interview. Its name preferencing informanpurposive sampling.The result of roll loan giving program PNPM urban private towards smalland medium enterprises in Bulusulur village, Wonogiri district, Wonogiri regencyshowed that this program was able to reached the purposes and targets throughedstandart dimension and policy's goal, implementation sources, communication,implementor agency characterictics, implementor disposition, and environmentalcondition towards sosial,economy and politics. The loan giving program has beenassisted the lowest societies in giving loan modal towards the small enterprisesand also assisted to improved the family's income. Yet in this case is still facedmany obstacles. Such as the less of loan or KSM within giving back of loan, andthere's no an available ingredients in that surrounding.Recomendation.this research is expected to be able keep along andincrease the same program, and build closer relationship between implementor,all target communities and founding the other new enterprises.Keywords : Program impelementation, Loan Revolving, Small and MediumEnterprises, Village of Bulusulur.